A highly sensitive PNA‐microarray system for miRNA122 recognition. Issue 6 (31st March 2022) - Forte, Giuseppe; Ventimiglia, Giorgio; Pesaturo, Massimiliano; Petralia, Salvatore
Abstract: Surface chemistry is a fundamental aspect of the development of the sensitive biosensor based on microarray technology. Here, an advanced PNA‐microarray system for the detection of miRNA, composed by a multilayered Si/Al/Agarose component, is described. A straightforward optical signal enhancement is achieved thanks to a combination of the Al film mirror effect and the positive interference for the emission wavelength of the Cy5 fluorescent label tuned by the agarose film. The PNA‐microarray was investigated for the detection of miRNA_122, resulting in a sensitivity of about 1.75 μM –1 and Limit of Detection in the range of 0.043 nM as a function of the capture probe sequence. The contribution, in terms of H‐bonds amounts at 298 and 333 K, of the agarose coating to the dsPNA‐RNA interactions was demonstrated by Molecular Dynamic simulations. These results pave the way for advanced sensing strategies suitable for the environmental monitoring and the public safety. Graphical Abstract and Lay Summary: In this study there cognition of miRNA by surface hybridization reaction with ssPNA microarray was demonstrated. The high sensitivity is achieved by the multilayer substrate (Si/Al/agarose) which combine the mirror effect of the Al film and the agarose coating chemistry.